Pengaruh Kinerja Kepala Madrasah dan Kinerja Guru Terhadap Mutu Lulusan - Wenison, Wenison (Journal of Innovation in Teaching and Instructional Media, 2025)
This study aims to analyze the influence of the performance of the madrasah principal and teacher performance on the quality of student graduates at MA YPGS Gunung Batu. This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and document analysis. The results of the study indicate that the performance of the madrasah principal and teacher performance have a significant influence on the quality of graduates. An effective madrasah principal in school leadership and management can improve teacher motivation and performance, which in turn has a positive impact on student achievement. Recommendations from this study include improving training and professional development for madrasah principals and teachers and implementing policies that support a conducive learning environment.